Welfare Implications of Inventory-Driven Dynamic Pricing - Stamatopoulos, Ioannis; Chehrazi, Naveed; Bassamboo, Achal (Management Science, 2019)
We argue that dynamic pricing motivated by the management of inventory holding and ordering costs leads to increased operational efficiencies that could benefit firms without hurting consumers. To demonstrate this point, we equip the traditional economic order quantity (EOQ) setting with a rich set of demand models and compare social outcomes under two alternatives, dynamic and static pricing. We show that dynamic pricing generates higher retailer profits, a lower average price per unit sold, and higher sales volumes than static pricing. The mechanism behind the result is that with dynamic pricing the retailer ties the price of each unit to its holding costs, which allows him to increase the order quantity compared with static pricing and thus save on fixed ordering costs. Some of these cost savings are passed to consumers. Moreover, we demonstrate that this mechanism is robust to the presence of price-anticipating (strategic) consumer behavior. This paper was accepted by Serguei Netessine, operations management.